ANALISIS BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL SPLTV DI SMA NEGERI 3 PONTIANAK - Raudhah, Siti; Hartoyo, Agung; Nursangaji, Asep (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to describe students' critical thinking in solving SPLTV problems at SMAN 3 Pontianak. The critical thinking criteria in this study used the FRISCO criteria (Focus, Reason, Inference, Situation, Clarity, Overview). Students are said to be ideal critical thinking if they meet the six criteria, and students are said to not have ideal critical thinking if there is one criterion that is not met. The research method used in this study in the qualitative with the descriptive type. Data collection techniques were written tests and interviews with data collection tools critical thinking tests and unstructured interview. The research subjects were 30 students of class X IPA 2 at SMAN 3 Pontianak. The results of the research obtained were that no one student could fulfill the six FRISCO criteria in the analyzing indicator and the evaluating indicator. This means that it can be concluded that the almost student's critical thinking is not ideal, because the criteria that appear only focus, clarity and overview. Â Â Keywords: Critical Thinking, FRISCO, HOTS